PROFESIONALLISME DAN KOMPETENSI MUTU GURU PADA PROSES PEMBELAJARAN TINGKAT SD, SMP, SMU DINAS PENDIDIKAN PROPINSI JAWA BARAT - Karna Husni (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2023)
Professionalism in the learning process should be a demand that must be met for teachers in teaching. This criticism has been made by many parties, so it is something that is reasonable to be addressed wisely and prudently by interested parties. Where the concept of a professional teacher will always be associated with knowledge of educational insights and policies, learning and learning theory, educational research (classroom action), learning evaluation, educational leadership, classroom/school management, as well as information and communication technology. For this reason, the role of the teacher is highly demanded in determining efforts to improve the quality of formal education. This means that the gum which is a learning agent must be able to carry out the learning process as well as possible, in supporting educational development. Therefore, teachers need to be developed as a dignified profession, as mandated in Permandinas No. 16 of 2007 concerning Academic Qualification Standards and Teacher Competency dated May 4 2007. Where it is stated that teacher competency standards are fully developed from the four main competencies, namely pedagogical, personality, social and professional competencies. In Law no. 14 of 2005, professional means the work or activity of a person and is a source of income for life that requires expertise, skills or skills that meet certain quality standards or norms and requires professional education. Professionals are (1) concerned with professions (fields of work based on certain expertise education); (2) requires special intelligence to run it; (3) requires payment to do so. Problems and challenges in the era of globalization demand an increase in the quality of democratization, transparency, quality culture and human rights. The development of IMTAQ and the acceleration of science and technology require quality human resources who are able to go international. The free market requires all nations to prepare quality human resources so they are not dependent on other nations. Quality human resources capable of facing international competition is only possible through quality education.